Electropolymerization of hydrogen bond supramolecular associations between terthiophene‐3‐acetic acid and 4, 4′‐bipyridine. Issue 10 (17th July 2017) - Beouch, Layla; Boileau, Sylvie; Chevrot, Claude; Tran‐Van, François
Abstract: Supramolecular assemblies based on 4, 4′‐bipyridine as hydrogen acceptor and a terthiophene carboxylic acid (3‐TTAA) as hydrogen donor were synthesized and characterized by Fourier transform IR spectroscopy and DSC. Their electropolymerization was successful in methylene chloride or acetonitrile. The concept of using such supramolecular assemblies in electropolymerization opens the way to the facile synthesis of new π‐conjugated polymers. © 2017 Society of Chemical Industry Abstract : In order to electropolymerize 3 tertiophene acetic acid (3‐TTAA) as well as hydrogen molecular assemblies between 3‐TTAA and 4, 4′ bipyridine (Bipy), the electroactivity of each monomer was studied from thin film of each monomer previously deposited on platinum electrode. The study reveals that the electroactivity of each assembly (ratio Bipy/3‐TTAA = 1 or 2) is drastically improved compared to that of 3‐TTAA alone. After electropolymerization, the hydrogen bonding remains showing that this way is a promizing way of electropolymerization of monomer possessing reactive group.